1982
DOI: 10.1063/1.93114
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization of Si on amorphous substrates by doughnut-shaped cw Ar laser beam

Abstract: Articles you may be interested inElectro-optical characteristics of omnidirectional liquid crystal domain mode using doughnut-shaped slit electrodes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 3 publications
0
24
0
1
Order By: Relevance
“…Therefore, as the pulse number or pulse energy increases, the NIR absorptance decreases after reaching a maximum value. The silicon amorphous structure goes back to silicon crystalline structure under the influence of laser irradiation [15][16][17][18][19][20][21][22][23][24][25][26]. The silicon structure can be changed back and forth between crystalline and amorphous by controlling the experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as the pulse number or pulse energy increases, the NIR absorptance decreases after reaching a maximum value. The silicon amorphous structure goes back to silicon crystalline structure under the influence of laser irradiation [15][16][17][18][19][20][21][22][23][24][25][26]. The silicon structure can be changed back and forth between crystalline and amorphous by controlling the experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, amorphous silicon-related papers of laser irradiation mainly concentrated on the application of the laser-annealing effect, i.e., amorphous silicon became silicon crystalline or micro/nanostructured silicon for better optoelectronics applications [15][16][17][18][19][20][21][22][23][24][25][26]. On the other hand, amorphous silicon and lattice distortions could be formed with the femtosecond laser irradiation [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…For solar cells, grains larger than the film thickness are required, that is grains above 10 Am in size. This can be achieved by a cw laser zone melting process operating at a wavelength in the visible range [4]. By optimizing the process parameters such as beam cross section and scanning rate areas with crystallites even larger than 100 Am have been prepared [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although narrow grains longer than 600 mm were obtained using a doughnut-shaped cw Ar laser beam, big grain growth over large areas was restricted [17]. Moreover, it was reported that a uniform poly-silicon film with large (B2 mm) aligned grains was formed using a technique based on a two-pass excimer laser re-crystallization process [18].…”
Section: Introductionmentioning
confidence: 98%